Forecasting demand for long-term care based on multistate piecewise constant Markov process - Xiaodong, Cui; Yuhua, Zheng (Economic Journal of Emerging Markets, 2018)
This paper forecasts demand for long-term care based on multistate piecewise constant Markov process. Two types of data are mainly used in this study. The first type of data came from the Chinese Longitudinal Healthy Longevity Survey (CLHLS), 2008-2011. The second type of data came from the China’s Demographic Yearbook of 2016, used as the number of population in the base period. It finds that the changes in health have a significant difference in gender and age. It also finds that under different health states, the distribution of duration of staying in each state in different gender and age groups shows a characteristic similar to the distribution of population size.